Fitness-to-drive for glioblastoma patients - Silvia Hofer; Kristina Keller; Lukas Imbach; Ulrich Roelcke; Gregor Hutter; Thomas Hundsberger; Caroline Hertler; Emilie Le Rhun; Flavio Vasella; Dominik Cordier; Marian Neidert; Andreas Hottinger; et al. (Swiss Medical Weekly, 2021)
OBJECTIVE